Insulin Signaling and Insulin Resistance Facilitate Trained Immunity in Macrophages Through Metabolic and Epigenetic Changes - Ieronymaki, Eleftheria; Daskalaki, Maria G.; Lyroni, Konstantina; Tsatsanis, Christos (Frontiers in Immunology, 2019)
Adaptation of the innate immune system has been recently acknowledged, explaining sustained changes of innate immune responses. Such adaptation is termed trained immunity. Trained immunity is initiated by extracellular signals that trigger a cascade of events affecting cell metabolism and mediating chromatin changes on genes that control innate immune responses. Factors demonstrated to facilitate trained immunity are pathogenic signals (fungi, bacteria, viruses) as well non pathogenic signals such as insulin, cytokines, adipokines or hormones. These signals initiate intracellular signaling cascades that include AKT kinases and mTOR as well as histone methylases and demethylases, resulting in metabolic changes and histone modifications. In the context of insulin resistance, AKT signaling is affected resulting in sustained activation of mTORC1 and enhanced glycolysis. In macrophages elevated glycolysis readily impacts responses to pathogens (bacteria, fungi) or danger signals (TLR-driven signals of tissue damage), partly explaining insulin resistance-related pathologies. Thus, macrophages lacking insulin signaling exhibit reduced responses to pathogens and altered metabolism, suggesting that insulin resistance is a state of trained immunity. Evidence from Insulin Receptor as well as IGF1Receptor deficient macrophages support the contribution of insulin signaling in macrophage responses. In addition, clinical evidence highlights altered macrophage responses to pathogens or metabolic products in patients with systemic insulin resistance, being in concert with cell culture and animal model studies. Herein, we review the current knowledge that supports the impact of insulin signaling and other insulin resistance related signals as modulators of trained immunity.